(untitled) (Agro Productividad, 2022)
Objective: To analyze available information about constructed wetlands and to identify the design, substrate, and vegetation advantages that could be an alternative solution to pig production system wastewaters. Design/methodology/approach: A broad literature review was conducted to identify the main characteristics of constructed wetlands (CWs), as well as the various plant species associated with these systems, and the substrates used as filter beds. Results: Vertical CWs have provided the best organic matter removal results, estimated indirectly through chemical oxygen demand (COD) and nitrogen derivatives such as total nitrogen (TN), ammonium (NH3), nitrate NO3 − ( ), and nitrite NO2 − ( ). Several substrates are used as filter beds, but they must be evaluated according to their availability, cost, and feasibility for colonization by nitrifying and denitrifying bacteria to degrade the dissolved pollutants. Combinations of plant species can reduce more than 10% of nitrogen products and organic matter. Study limitations/implications: The lack of monitoring for the satisfactory application of water care standards by small backyard and transition producers limits the adoption of environmental technologies for livestock sustainability in Mexico. Findings/conclusions: Constructed wetlands are inexpensive, easy-to-use, adaptive systems that can be feasible alternatives for reducing the pollution caused by the swine wastewater generated by backyard producers Objetivo: Analizar la información generada acerca de los humedales construidos e identificar las ventajas de los diseños, sustratos y vegetación para su utilización como alternativa de solución a las aguas residuales de sistemas de producción porcina. Diseño/metodología/acercamiento: Se realizó una revisión amplia de literatura, y se identificaron las características principales de los humedales construidos (HC); así como la participación de diversas especies de plantas asociadas a estos sistemas, y los sustratos que han sido utilizados como lecho filtrante. Resultados: Los HC verticales han obtenido los mejores resultados en la remoción de materia orgánica, estimada indirectamente por medio de la demanda química de oxígeno (DQO), y derivados del nitrógeno como nitrógeno total (NT), amonio (NH3), nitrato (NO3) y nitrito (NO2). Diversos sustratos se pueden utilizar como lecho filtrante, pero deben ser evaluados conforme a la disponibilidad, costo, y factibilidad de colonización de bacterias nitrificantes y desnitrificantes para la degradación de sustancias contaminantes disueltas. Las especies vegetales permiten reducir más del 10% de los productos del nitrógeno y la materia orgánica presente. Limitantes del estudio/implicaciones: La falta de vigilancia de la aplicación de las normas para el cuidado del agua en pequeños productores de traspatio y transición limita la adopción de tecnologías ambientales para la sostenibilidad pecuaria en México. Hallazgos/conclusiones: Los HC son sistemas económicos de fácil utilización y adaptación que pueden ser una alternativa factible para reducir la contaminación por aguas residuales porcinas de productores de traspatio.